Autocuidado emocional relacionado con estrés académico en estudiantes universitarios - Romero Pérez, Betsaida Marisol (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
Introduction. The training process is a learning experience that is usually accompanied by stress and requires an effort to adapt from the student. Various authors mention that students in the health area have significantly higher levels of academic stress than students in other disciplines. Objective. Analyze the relationship between emotional self-care and academic stress in university students. Methodology. This study used a quantitative, descriptive approach, with a non-experimental, correlational and transversal design. The universe contemplated for this study were the students of the Faculty of Nursing of the UMSNH, in the city of Morelia Michoacán. The sample was simple random at the convenience of 318 students from the first, third, fifth and seventh semester. To measure emotional self-care, the self-care behavior scale (ECA) was used, with 52 items, with a reliability of ?=0.94. On the other hand, to measure academic stress, the SISCO inventory was used, consisting of 31 items, with a reliability of ?=0.90. The study was approved by the Ethics and Research Committee of the Faculty of Nursing. Results. It was found that 81.8% of the participants were women, 65.7% reported having moderate emotional self-care on their total scale, and 78.7% presented moderate academic stress. When analyzing the relationship between emotional self-care and academic stress in university students, for which the Rho Spearman statistical test was used, finding that the total scale did not present statistical significance, therefore the research hypothesis was rejected, as there was no evidence enough to affirm that there is a significant positive correlation between emotional self-care and academic stress. Conclusion. Based on the information obtained, it is necessary to continue studying or carry out educational interventions to strengthen emotional self-care related to academic stress to develop satisfactory educational learning.

Introducción. El proceso de formación es una experiencia de aprendizaje que suele estar acompañada de estrés y requiere del estudiante un esfuerzo de adaptación. Diversos autores mencionan que los estudiantes del área de la salud tienen niveles de estrés académico significativamente mayores que los estudiantes de otras disciplinas. Objetivo. Analizar la relación entre autocuidado emocional y estrés académico en universitarios. Metodología. Enfoque cuantitativo, con diseño no experimental, correlacional y transversal. El universo contemplado para este estudio fueron los estudiantes de la Facultad de Enfermería de la UMSNH, de la ciudad de Morelia Michoacán. La muestra fue probabilística y aleatoria simple, por 318 estudiantes de primer, tercer, quinto y séptimo semestre. Para medir el autocuidado emocional se utilizó la escala de conductas de autocuidado (ECA), con 52 ítems y α=0.94. Para medir el estrés académico se utilizó el inventario SISCO, configurado por 31 ítems, con una confiabilidad de α=0.90. El estudio fue aprobado por el Comité de Investigación y Ética en Investigación de la Facultad de Enfermería. Resultados. Se encontró que el 81.8% de las participantes fueron mujeres, 65.7% refirieron tener un autocuidado emocional moderado en la escala total, el 78.7% presentan estrés académico moderado. Al analizar la relación entre autocuidado emocional y estrés académico en estudiantes universitarios, encontrando que en la escala total no presento significancia estadística, por lo que se rechaza la hipótesis de investigación, al no existir evidencia suficiente para afirmar que existe una correlación positiva significativa entre autocuidado emocional y estrés académico. Conclusión. Es necesario continuar estudiando o realizar intervenciones educativas para fortalecer el autocuidado emocional relacionado al estrés académico para desarrollar un aprendizaje educativo satisfactoriamente.
Facultad de Enfermería. Maestría en Enfermería
Keywords: info:eu-repo/classification/cti/3; FE-R-M-2024-1346; Salud pública; Autocuidado emocional; Estrés académico; Universitarios; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18895